Bankruptcy Procedure for Individuals in Russia and the USA: Comparative Legal Analysis - Sinenko, Vladimir S.; Rubanov, Sergey A.; Lilikova, Oksana S.; Gordeev, Aleksey Yu (Cuestiones Políticas, 2020)
Bankruptcy is the legitimate procedure by which monetarily troubled firms, people, and sporadically governments settle their obligations. The insolvency procedure for firms assumes a focal job in financial aspects, since rivalry drives the most wasteful firms bankrupt, subsequently raising the normal proficiency level of those remaining. This study provides a comparative analysis of the most significant aspects of bankruptcy for individuals in Russia and the United States. The objective of the study was to determine the conditions involved in declaring a citizen insolvent in US and Russian law, for which we studied the ways of filing applications in these countries, as well as some methods of abuse by creditors that reduce the effectiveness of the bankruptcy institution, and the ways to minimize them. Based on the results of the analysis, proposals were made to improve the legislation that governs people’s bankruptcy. These proposals are based on the positive experience of the United States in the field of legal regulation of insolvency institutions.